Article 41 of the Italian Constitution and the Italian Model of Corporate Social Responsibility - Paolo RICCI (Revista de Management Comparat International)
Article 41 of the Italian Constitution is composed of three important provisions: the first one establishes the principle of free economic activity, the second one is about its limitations while the third one sets out the way public intervention – seen as necessary to the direction and co-ordination of economic activity – may take place. A pro